Internalizing the Values of Religious Moderation through Narrative Education: A Study among Madrasah Aliyah Students in Pekalongan - Abdul Khobir; Abdul Basith; Hendri Hermawan Adinugraha; Ilyas Erpay (International Journal of Educational Narratives, 2026)
Background. The rise of exclusive and radical religious narratives among Indonesian students, driven by globalization and digitalization, poses a serious threat to social cohesion. Madrasah in Pekalongan, as strategic Islamic educational institutions, face the challenge that a purely cognitive approach to learning is insufficient to foster deep awareness of anti-extremism among students. Purpose. This research analyzes the process of internalizing religious moderation values through narrative education and its implications for fostering anti-extremist awareness among madrasah students in Pekalongan. Methods. This study employed a qualitative case study design involving purposively selected teachers and students in Pekalongan madrasah. Data were collected through in-depth interviews, participatory observation, and documentation. Data analysis was conducted thematically through data reduction, categorization, interpretation, and conclusion drawing. Data validity was ensured through triangulation and member checking to strengthen credibility. Results. Findings show that narrative education through experiential stories, role modeling, and reflective dialogue engages both emotional and cognitive dimensions of students more effectively than cognitive approaches alone. Students are able to construct their own understanding of moderation values (tawasuth, tasamuh, tawazun, i’tidal) through lived experiences rather than passive acceptance. This process strengthens anti-extremist awareness and builds resilience against radical influences in the learning environment. Conclusions. Narrative education is an effective pedagogical strategy for internalizing religious moderation values and developing anti-extremism awareness. It integrates reflective dialogue and exemplary storytelling to foster meaningful understanding and can be adopted as an innovative approach in madrasah education.